Adsorptive properties of mesoporous silica modified with Lewis base molecule and its application in the preconcentration of Cu(II), Co(II), and Cd(II) from aqueous media - Ivassechen, Janaíne do Rócio [UNESP]; Jorgetto, Alexandre de Oliveira [UNESP]; Wondracek, Marcos Henrique Pereira [UNESP]; Silva, Adrielli Cristina Peres da [UNESP]; Zara, Luiz Fabrício; Pedrosa, Valber de Albuquerque [UNESP]; Rocha, Bruno Prior [UNESP]; Saeki, Margarida Juri [UNESP]; Castro, Gustavo Rocha [UNESP] (The Scientific and Technological Research Council of Turkey (TUBITAK-ULAKBIM) - DIGITAL COMMONS JOURNALS, 2018)
Cocondensation and postfunctionalization methods were employed to synthesize a mesoporous silica with large surface area (795.1 ± 1.1 m2 g− 1) modified with 4-amino-5-hydrazino-1,2,4-triazole-3-thiol, which was successfully applied to adsorb and preconcentrate Cu(II), Co(II), and Cd(II) from aqueous media. Infrared spectroscopy of the adsorbent material demonstrated N-H stretching bonds related to primary amines existing in the ligand molecule, elemental analysis revealed the presence of 0.132 mmol g− 1 of nitrogen, scanning electron microscopy indicated globularly shaped particles with average size of 10 µm, and the point of zero charge was found to be 7.2. Kinetic data were applied to the pseudo-second-order model, indicating that a chemisorption mechanism is probably involved in the uptake of metal ions from aqueous solutions. According to the Langmuir model, the adsorption capacities for the different ions obey the following order: Cu(II) > Co(II) > Cd(II). Through a preconcentration system, a preconcentration factor of 18-, 15-, and 20-fold was attained for Cu(II), Cd(II), and Co(II), respectively. The proposed method was applied in the determination of trace metals in natural river water (Tietê River) and the results were validated through standard reference material analysis. The results also indicated that the packed column proved to be stable over 24 adsorption/desorption cycles, demonstrating that the developed material is potentially suitable for the determination of trace-level metal ions in aqueous samples.
Keywords: Cocondensation method; Metal adsorption; Modified surface; Preconcentration